Adolescents' Perception of Asthma Symptoms and Health Care Utilization - Rhee, Hyekyun; Belyea, Michael J.; Halterman, Jill S. (Journal of pediatric health care, 2011)
Pediatric asthma is accountable for a substantial use of health care services. The purpose of this study was to systemically examine the extent to which inaccurate perception of asthma symptoms is associated with the use of health care services. This exploratory study included 126 adolescents with asthma who were between 13 and 20 years of age. Subjects were classified as having inaccurate symptom perception (IG); well-controlled accurate symptom perception (WCA); and poorly controlled accurate symptom perception (PCA). These groups were compared with respect to health care utilization, including emergency department (ED) visits, hospitalization, and office visits and school absenteeism in the past 3 months. More adolescents in the IG group had at least one hospitalization compared with adolescents in the PCA or WCA groups (23.1% vs. 11.1% vs. 2.6%, respectively). A similar trend was seen for ED visits. Compared with the WCA group, adolescents in the IG group were nearly nine times more likely to have been hospitalized, 3.4 times more likely to have visited an ED, and four times more likely to have missed school days. Adolescents with inaccurate symptom perception are more likely to have hospitalizations, ED visits, and missed days from school compared with those who have accurate perceptions. The findings underscore the importance of screening for perceptual accuracy of asthma symptoms and call for interventions promoting accurate symptom assessment in adolescents with asthma to ensure appropriate care.